2016
DOI: 10.1186/s12974-016-0628-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 signaling is essential to attenuate viral-induced encephalitis development by downregulating iNOS expression in the central nervous system

Abstract: BackgroundViral encephalitis is a common cause of lethal infections in humans, and several different viruses are documented to be responsible. Rocio virus is a flavivirus that causes a severe lethal encephalitis syndrome in humans and also mice, providing an interesting model to study the CNS compartmentalized immune response. Interleukin 33 (IL-33), a member of the IL-1 family, is an immunomodulatory cytokine that is highly expressed in the CNS. However, the role of IL-33 on viral encephalitis remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…In addition, IL-33 was also reported to be essential to attenuate viral-induced encephalitis [41]. In line with these reports, enhanced expression of IL-33 in mice was suggested to mediate T reg cell expansion and protection by IVIG [19, 20, 27].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, IL-33 was also reported to be essential to attenuate viral-induced encephalitis [41]. In line with these reports, enhanced expression of IL-33 in mice was suggested to mediate T reg cell expansion and protection by IVIG [19, 20, 27].…”
Section: Discussionmentioning
confidence: 92%
“…Leukocytes in the brain were isolated as previously described [14,24]. Leukocyte purification and quantification of cytokines and chemokines are briefly described in the Supplementary Methods.…”
Section: Leukocyte Isolation From Cns Specimens and Flow Cytometrymentioning
confidence: 99%
“…Previously, it was reported that levels of multiple leukocytes, such as CD8 + T lymphocytes, macrophages, neutrophils, and CD45R + B lymphocytes, were elevated in response to ROCV infection in the CNS of BALB/c mice [13,14]. However, no leukocyte population was assessed in blood specimens in an animal model.…”
Section: Peripheral Bloodmentioning
confidence: 99%
See 2 more Smart Citations